Politik Hukum Penegakan Tindakan Korupsi Dimasa Pandemi Covid-19 - Muhammad al ikhwan Bintarto; Ramy Abubakri Akhirul Zulhaj (Jurnal Ilmu Hukum, 2021)
Corruption is an immoral act contradict the law which is all of part can’t agree with this doing and can scathe the finances and economy a country, corruption can be carried out in all aspects of society from the lower classes to the upper classes. Corruption in Indonesia in 2020 increased according to ICW even though it was still in the Covid-19 pandemic which presiden was designated thic pandemic as a non-natural disaster, then can point 1 and 2 in Anti-Corruption Laws be implemented during a pandemic The purpose of this study is to explain how the legal policy of enforcing corruption during covid-19 pandemic and how to implement the Anti-Corruption Law point 1 and 2 when pandemic era. This study uses normative research so that it can provide an assessment of a legal action and The data for this research collected from laws and regulations, books, journals, etc. And the results of this study want to know how to enforce corruption in Indonesia when the covid-19 pandemic